Cricoid Chondronecrosis: Case Report and Review of Literature. (July 2020) - Mims, Mark M.; Leclerc, Andree A.; Smith, Libby J.
Objective: Cricoid chondronecrosis is a rare entity that has significant consequences for patients. Reports of its occurrence are scattered in the literature and currently there is no comprehensive review to help guide providers. Methods: A case report from our institution is presented. A review of available literature is then provided with assessment of risk factors, signs and symptoms at presentation, laryngeal exam findings, radiologic findings, and surgical techniques. Results: Twenty-four cases of cricoid chondronecrosis were reviewed from the literature. Patient age ranged from 8 months to 76 years. A history of endotracheal intubation for various reasons was present in all but two cases, and duration of intubation ranged from 6 hours to 28 days. Patients presented with airway compromise in all but two cases—one asymptomatic patient with prior tracheostomy and another with dysphagia after radiation. Dysphonia (n = 6) and dysphagia (n = 3) were less commonly present. Subglottic stenosis (n = 19) was the most common exam finding followed by vocal fold impairment (n = 11). When CT scan findings were reported, fragmentation of the cartilage and/or hypodensity of the central lamina were described in all but one case. Interventions ranged from observation on antibiotics and steroids to surgical therapies including tracheostomy, dilation, and posterior cricoid split, with or without stent placement. Conclusions: Cricoid chondronecrosis is a serious, rare entity that can occur even after a short period of endotracheal intubation. Providers must have a high level of suspicion in patients that present with upper airway dyspnea with a history of prior intubation. Level of evidence: Level 4